2015
DOI: 10.1021/bi5012942
|View full text |Cite
|
Sign up to set email alerts
|

Axial Hydrogen at C7 Position and Bumpy Tetracyclic Core Markedly Reduce Sterol’s Affinity to Amphotericin B in Membrane

Abstract: The interaction of amphotericin B (AmB) with fungal ergosterol (Erg) is stronger than its interaction with mammalian cholesterol (Cho), and this property of AmB as an antifungal drug is thought to be responsible for its selective toxicity toward fungi. However, the mechanism by which AmB recognizes the structural differences between sterols, particularly minor difference in the sterol alicyclic portion, is largely unknown. Thus, to investigate the mode of interaction between AmB and the sterol core, we assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 65 publications
0
20
0
Order By: Relevance
“…Ergosterol has been proposed as a target molecule in the medical treatment of fungal infections, following mainly two routes: (i) the inhibition of the biosynthesis of ergosterol, as in the case of ketoconazole and clotrimazole drugs action, and (ii) direct interaction, as in the case of amphotericin B, where two reaction mechanisms have been proposed . The first mechanism proposed for direct interaction of ergosterol with amphotericin B has been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Ergosterol has been proposed as a target molecule in the medical treatment of fungal infections, following mainly two routes: (i) the inhibition of the biosynthesis of ergosterol, as in the case of ketoconazole and clotrimazole drugs action, and (ii) direct interaction, as in the case of amphotericin B, where two reaction mechanisms have been proposed . The first mechanism proposed for direct interaction of ergosterol with amphotericin B has been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 As shown in Figure S17, this absorption was observed only for the AmB/ergosterol membrane while the 4/ergosterol preparation showed the peak not at 415 but at 408 nm; the spectra implied that 4 has lower affinity to ergosterol, and thus its channel assembly is probably less stable than that of AmB. 8,36,37 Another possible explanation is that the extended conformation enhances the stability of large aggregates in water (Fig. S16), which prevent the analog to bind to membrane.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, we have reported the SAR results of various sterol analogs, and found that the AmB-ergosterol interaction is probably stabilized by face-face VDW interaction. 7,8 Thus, the gauche-containing conformation induced by 7a-OH-AmB may prevent the VDW contact between the AmB macrolide and sterol, consequently altering the sterol selectivity of 3 ( Fig. 3f/g).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these distance data as well as our previous structure-activity relation study [148], a geometry search for AmB and Erg complexes was performed and the most likely geometries for the AmB-Erg complex were obtained for the parallel and antiparallel orientations (Fig. 14] [147].…”
Section: Dynamics Of Amphotericin B and Sphingomyelin In Membrane Bilmentioning
confidence: 99%